Detection of EGFR gene mutations in circulating DNA by liquid biopsy in patients with non-small cell lung cancer: Brief review - Egoavil Guerra, Marina Janeth (2021)
Lung cancer is a public health problem due to its high morbidity and mortality worldwide and in Peru. In non-small cell lung cancer, the detection of mutations of the epidermal growth factor receptor (EGFR) has been useful for the choice of therapeutics for this disease. In the present article we aim to discuss current and relevant information on the best diagnostic technique for EGFR in patients with non-small cell lung cancer. The main cancer guidelines and two systematic reviews showed evidence in favor of the diagnosis of EGFR gene mutations on liquid biopsy as an alternative to tissue biopsy at the beginning of diagnosis and with a greater acceptance use, in the clinical setting of NSCLC patients with sensitive EGFR mutations. This healthcare technology may be useful in our country, and we propose its use in two clinical scenarios.